2017
DOI: 10.1177/1941738117730576
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis Prophylaxis in Anterior Cruciate Ligament Reconstructive Surgery: What Is the Current State of Practice?

Abstract: Background:Venous thromboembolism (VTE) is a significant perioperative risk with many common orthopaedic procedures. Currently, there is no standardized recommendation for the use of VTE prophylaxis during anterior cruciate ligament (ACL) reconstruction. This study sought to evaluate the current prophylactic practices of fellowship-trained sports medicine orthopaedic surgeons in the United States.Hypothesis:Very few surgeons use perioperative VTE prophylaxis for ACL reconstructive surgery.Study Design:Survey.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
1
14
0
4
Order By: Relevance
“…Previous work suggested that while antibiotic prophylaxis is routine in most countries, VTE prophylaxis rates vary from around 17% in Norway and 51% in the United States to 79% in Denmark. 17,21 The findings in this study may support further investigation and consideration of routine VTE prophylaxis in this population.…”
Section: Discussionsupporting
confidence: 55%
“…Previous work suggested that while antibiotic prophylaxis is routine in most countries, VTE prophylaxis rates vary from around 17% in Norway and 51% in the United States to 79% in Denmark. 17,21 The findings in this study may support further investigation and consideration of routine VTE prophylaxis in this population.…”
Section: Discussionsupporting
confidence: 55%
“…20,23 Despite DVT being a significant complication after lower extremity orthopaedic procedures, only 50% of sports medicine fellowship–trained surgeons routinely utilize thrombus prophylaxis in ACL reconstruction. 31 Because of the lack of a standardized protocol for thrombus prophylaxis, clinical experience and personal opinion are the primary factors for determining usage and dosage protocols. Age older than 35 years, nicotine use, tourniquet time longer than 2 hours, surgery at higher elevations, and concomitant high tibial osteotomy or posterior cruciate ligament reconstruction have been associated with an increased risk of thrombus formation after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Although these guidelines do not extend to nonarthroplasty procedures, chemoprophylaxis is still prescribed routinely for other lower extremity operations, such as anterior cruciate ligament reconstruction (ACLR). According to the survey results by Keller et al, 17 50.7% of sports medicine fellowship–trained surgeons use chemoprophylaxis following ACLR to protect against the occurrence of VTE; the majority of these surgeons use aspirin, with wide variation in both the dose and duration of treatment.…”
mentioning
confidence: 99%